Karyawan: Kepuasan Kerja dan Organizational Citizenship Behavior - Rifqi, Ghozi (Peneliti.net, 2024)
Employees are individuals who are the main wealth for every company. Employees in a company who are deployed become planners and controllers who always play an active role and realize the company's goals. Employees who have high job satisfaction will develop OCB attitudes. The aim of this research is to empirically determine the influence of OCB job satisfaction on employees. The population is employees who work in Jabodetabek and have worked for at least 1 year. Data collection was obtained using OCB and job satisfaction questionnaires. The research results show that job satisfaction influences OCB with a sig value of 0.000. Based on the R Square value of 0.358, which means job satisfaction contributes 35,8% to OCB. There is a positive regression coefficient value of 0.482 which shows that there is a positive and significant influence between job satisfaction and OCB.